Digital Literacy of Students: Methodology, Testing, Assessment - Elena K. Kalashnikova; Egor K. Karpov (Вопросы образования)
Digital transformation of education is a trend driven by economic development and supported at the federal level. Various ways of developing digital literacy are present at all levels of education, but after graduating from school, applicants come to university with different levels of skills and competencies. For a university, determining and aligning the level of students' digital literacy is a need that ensures further effective learning and building an individual trajectory. In this article, a methodology for assessing digital literacy has been developed, meeting the needs of the university. A diagnostic study was conducted among first-year students at Tyumen State University, and a prototype "digital literacy profile" for students was developed. Testing was carried out in four types of literacy: informational, technological, media literacy, and communication; three aspects: cognitive, technological, and ethical; and two levels: basic and advanced. As a result of the study, individual profiles of digital literacy were obtained for more than two and a half thousand first-year students studying full-time. Lists of students with low and high levels of digital skills were formed. A support course in digital literacy was planned and implemented for the first group, and recommendations for choosing elective disciplines specializing in ICT were given to the second group.